Cubes of finite vertices fuzzy topographic topological mapping and k -Fibonacci sequence - Yunus A.A.M.; Ahmad T. (American Institute of Physics Inc., 2024)
Fuzzy Topographic Topological Mapping (FTTM) is a model for solving neuromagnetic inverse problem. FTTM consists of four components and connected by three algorithms. FTTM version 1 and FTTM version 2 were designed to present 3D view of an unbounded single current and bounded multicurrent sources, respectively. In 2008, Suhana introduced some definitions on sequence of FTTM. One of the features produced from the sequences of FTTM is Cube of FTTM. A cube of FTTM is a combination of two or more FTTM in FTTMn. In this paper, cube of finite vertices of FTTM, namely FKn are discussed. Consequently, some theorems are proven in order to describe patterns for sequence of cubes for FKn based on this k-Fibonacci sequence. Interestingly, the cube of FKn appears to be an example of generalized Fibonacci sequence, namely the k-Fibonacci sequence. 2018 Author(s).